PEMBELAJARAN ANDRAGOGI PADA PERGURUAN TINGGI ISLAM: ANALISIS PENGELOLAAN MANAJEMEN KELAS DAN STRATEGI PEMBELAJARAN - Rahmat Rifai Lubis; Nona Kumala Sari; Masruroh Lubis; Darwis Margolang (Jurnal Bilqolam Pendidikan Islam, 2024)
Islamic Higher Education has its own characteristics compared to public universities, although both implement andragogy, but the output of andragogy produced is certainly different from one another. Classroom management and learning strategies are one of the triggers of these differences. In this regard, this study aims to analyse andragogy learning at the Islamic College of Sumatra Medan, with a focus on classroom management and learning strategies. This research uses case study-based qualitative method. Data collection techniques used observation, interviews and documentation studies. The results revealed that the research at the Islamic College of Sumatra showed that the andragogy classroom management model that integrates Islamic principles and technology improves the learning experience and student motivation. The use of technology supports Multimedia Cognition theory, while strategies such as individual mentoring and collaborative methods are in line with Constructivism and Social Learning theories. Challenges such as change resistance and limited resources require effective managerial approaches. The research recommends the importance of change management and resource management to improve the implementation of the andragogy model.